Nonalcoholic fatty liver disease and insulin resistance in children - Kyungchul Song; Ho-Seong Kim; Hyun Wook Chae (The Korean Pediatric Society, 2023)
Nonalcoholic fatty liver disease (NAFLD), a spectrum of liver diseases characterized by excessive fat accumulation, is the leading cause of chronic liver disease. The global prevalence of NAFLD is increasing in both adults and children. In Korea, the prevalence of pediatric NAFLD increased from 8.2% in 2009 to 12.1% in 2018 according to a national surveillance study. For early screening of pediatric NAFLD, laboratory tests including aspartate aminotransferase and alanine aminotransferase; biomarkers including hepatic steatosis index, triglyceride glucose index, and fibrosis-4 index; and imaging studies including ultrasonography and magnetic resonance imaging are required. Insulin resistance plays a major role in the pathogenesis of NAFLD, which promotes insulin resistance. Thus, the association between NAFLD and insulin resistance, diabetes mellitus, and metabolic syndrome has been reported in many studies. This review addresses issues related to the epidemiology and investigation of NAFLD as well as the association between NAFLD and insulin resistance and metabolic syndrome with focus on pediatric NAFLD.